Spherical cobalt/cobalt oxide - Carbon composite anodes for enhanced lithium-ion storage. (20th February 2018) - Patrinoiu, Greta; Etacheri, Vinodkumar; Somacescu, Simona; Teodorescu, Valentin S.; Birjega, Ruxandra; Culita, Dana C.; Hong, Chulgi Nathan; Calderon-Moreno, Jose Maria; Pol, Vilas G.; Carp, Oana
Abstract: Herein we report a simple and scalable route to synthesize porous cobalt/cobalt oxide - carbon sphere composites as anode material for rechargeable lithium-ion batteries. It involves the impregnation of starch-derived hydrochar spheres with a cobalt salt, followed by a heat treatment (700 °C) under inert atmosphere. The obtained high surface area (∼670 m 2 g −1 ), submicron spheres (∼300 nm diameter) with high-degree of microporosity (81%) consist of an amorphous carbon matrix with embedded Co/CoO nanoparticles (∼6 nm sized), having a total cobalt content of 6.2 wt%. The hybrid sphere anodes demonstrated superior specific capacity, rate performance and cycling stability. Discharge capacities of 520 and 310 mA h g −1 are observed at charge-discharge rates of 0.1 and 1C respectively. No significant capacity fading is identified on prolonged cycling at various current densities. The electrode also demonstratedexcellent structural stability during extended charge-discharge processes. Graphical abstract: Highlights: Co/CoO (6.2 wt% Co) nanoparticles are embedded into microporous carbonaceous spheres. Hybrid sphere electrode retains a specific capacity 5-fold higher than graphite. Electrode exhibits excellent cyclic ability and structural stability/integrity.